2021
DOI: 10.2147/prbm.s324460
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Leader Behaviors and Followers Overall Justice and Citizenship Behaviors: The Role of Renqing Perception and Trait Agreeableness

Abstract: Purpose Drawing on the uncertainty management theory, this study explores the relationships between paradoxical leader behaviors (PLB) and followers perceptions of overall justice and organizational citizenship behaviors (OCB), as well as the mediating role of two components of followers perceptions of renqing (affective interaction and discretionary consideration) and the moderating role of trait agreeableness. Methods This study employed two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…We performed the analyses with SPSS 24 and AMOS 24 software. After performing confirmatory factor analysis in AMOS software, we followed numerous studies that used the Hayes Process plugin for mediation and moderated mediation analyses (Yang et al 2020 ; Zhou et al 2020 ; Jiatong et al 2021 ; Ren and Yang 2021 ; Liu et al 2022a , b ; Uysal et al 2022 ). For the data generated from the questionnaires, we employed various statistical analyses tools such as questionnaire reliability, descriptive statistics, differences (T-test and ANOVA), confirmatory factor, correlation, multiple regression, and mediation analyses.…”
Section: Methodsmentioning
confidence: 99%
“…We performed the analyses with SPSS 24 and AMOS 24 software. After performing confirmatory factor analysis in AMOS software, we followed numerous studies that used the Hayes Process plugin for mediation and moderated mediation analyses (Yang et al 2020 ; Zhou et al 2020 ; Jiatong et al 2021 ; Ren and Yang 2021 ; Liu et al 2022a , b ; Uysal et al 2022 ). For the data generated from the questionnaires, we employed various statistical analyses tools such as questionnaire reliability, descriptive statistics, differences (T-test and ANOVA), confirmatory factor, correlation, multiple regression, and mediation analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The basic premise of PLB is that leaders will confront ongoing, competing demands to meet both organizations' structural needs and followers' individual needs (Zhang et al, 2015). Most PLB studies employing survey designs measuring follower perceptions of PLB have found positive associations with outcomes including follower job attitudes (e.g., Zhang et al, 2015;Backhaus et al, 2022) and behaviors (e.g., Ren and Yang, 2021). However, there are also inconsistent (Ishaq et al, 2021;Qu et al, 2022) and conflicting findings, such as positive associations with follower job stress (Bashir, 2021) and mixed associations with follower creativity (e.g., Shao et al, 2019), suggesting that PLB may not always be desirable.…”
Section: Main E Ectsmentioning
confidence: 99%
“…24 There is a positive relationship between paradoxical leader behaviors and organizational citizenship behaviors. 25 Work engagement has a mediating role between workplace loneliness and organizational citizenship behaviors. 26 At the same time, according to the affective events theory, individuals' perceived work experience will trigger their emotional reactions, affecting the individual's psychology and behaviour and further affecting the organization's performance.…”
Section: The Mediating Role Of Negative Emotionsmentioning
confidence: 99%